Foreign aid resurgent: New spirit or old hangover? - Peter Burnell (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This study is premised on the view that reports circulating in the 1990s, claiming foreign aid was in terminal crisis, were premature. Aid's reviving fortunes are explained in terms both of a growing awareness of the uneven implications of globalization and the after-effects of the terrorist events of 11 September 2001. However these two `drivers' make uneasy partners. Furthermore, aid for democratization, argued in the 1990s to be an instrument for indirectly addressing socioeconomic weakness and improving development aid's effectiveness—making it a positive feature in a bleak decade—is increasingly seen as problematic. For now, aid's resurgence should target pro-poor development rather than democratic reform, although the likelihood is that old fashioned determinants of realpolitik will continue to get in the way.
Keywords: F35; O19; 330; foreign aid; international linkages to development; role of international organizations; Entwicklungshilfe; Entwicklungsorganisation